2011
DOI: 10.1007/s13233-011-0902-0
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular uptake of magnetite nanoparticles conjugated with RGDS-peptide

Abstract: Peptides containing the Arg-Gly-Asp (RGD) motif inhibit cell adhesion and exhibit a range of other biological effects including anticoagulant and antimetastatic activities. This study examined the anchorage independent effects of an RGD-containing peptide, Arg-Gly-Asp-Ser (RGDS), on NIH 3T3 fibroblasts. Magnetite nanoparticles were prepared by the coprecipitation of ferrous iron (Fe 2+ ) and ferric iron (Fe 3+ ) with NH 4 OH and dextran (DNPs). The aminosilane agent of 3-aminopropyltriethoxysilane (A) is consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…This suggests that the GM carrying folic acid provide specific recognition signals for the nanoparticles to facilitate internalization into the target cells (KB cells). Interaction of the folic acid-conjugated GM with the folate receptors expressed on the membrane surface of the KB cells might have contributed to the improved internalization of GF into the cells, through receptor-mediated endocytosis [ 27 ]. Gan et al .…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that the GM carrying folic acid provide specific recognition signals for the nanoparticles to facilitate internalization into the target cells (KB cells). Interaction of the folic acid-conjugated GM with the folate receptors expressed on the membrane surface of the KB cells might have contributed to the improved internalization of GF into the cells, through receptor-mediated endocytosis [ 27 ]. Gan et al .…”
Section: Resultsmentioning
confidence: 99%
“…GNPs showed an absorption onset at 386 nm and after herceptin immobilization, they exhibited a red shift to 389 nm. 26 This red shift was produced by strong quantum confinement due to the increase in particle size after metal-to-ligand charge transfer. 27 , 28 The surface modification of GNP with herceptin was also confirmed by FT-IR, as displayed in Figure 3 .…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the GM carrying folic acid provide specific recognition signals for the nanoparticles to facilitate internalization into the target cells (KB cells). Interaction of the folic acid-conjugated GM with the folate receptors expressed on the membrane surface of the KB cells might have contributed to the improved internalization of GF into the cells, through receptor-mediated endocytosis [27]. Gan et al reported similar results [28].…”
Section: Evaluation Of Intracellular Uptakementioning
confidence: 93%